PENGARUH LEVERAGE DAN FIRM SIZE TERHADAP PENGHINDARAN PAJAK (TAX AVOIDENCE) PADA PERUSAHAAN PROPERTY DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERATING - Ingrid Panjaitan (UNIVERSITAS 17 AGUSTUS 1945 jAKARTA, 2016)
This study aims to analyze pengaru leverage and firm size against tax evasion and profitability as a moderating variable and know the variables that have dominant influence by collecting data publication annual financial statements of property companies that have been listed on the BEI and in accordance with the criteria of sample selection. Independent variables are lerevage, firm size, dependent variable is tax avoidance and profitability as moderating variable. The research location was conducted in Jakarta. The population in this study are companies listed on the Indonesian stock exchange (IDX), but companies that do not match the criteria set by researchers will be removed from the sample. This research method using non participant observation technique and purposive sampling. Data obtained from BEI which then processed and analyzed by using SPSS data analysis. The results of this study indicate that the laverage variable has no significant effect on tax evasion. firm size variables have a negative and significant effect on tax evasion. This is not followed by leverage variables and firm size moderated profitability has no significant effect on tax evasion. Keywords: leverage, firm size, profitability, tax evasion.